Soil management practices for sustainable food production - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The Tropical Soil Biology and Fertility Programme (TSBF) was initiated in 1984 under the patronage of the Man and Biosphere (MAB) programme of UNESCO and the Decade of the Tropics initiative of TUBS. The programme goal is to develop appropriate and...